A new dilation model for FRP fully/partially confined concrete column under axial loading - Shayanfar, Javad (2021)
Experimental research has confirmed that the usage of fiber reinforced polymer (FRP) composite materials can be a reliable solution to substantially improve axial and dilation behavior of confined concrete columns. In this regard, FRP partial confinement system is a good compromise from the cost competitiveness point of the view, while the application of discrete FRP strips provides less confinement efficiency compared to full confinement system. Experimental observations demonstrated that the concrete at the middle distance between the FRP strips experiences more transversal expansion compared to concrete at the strip regions. It can result in a considerable decrease in the confinement performance in curtailing concrete transversal expansion, overwhelming the activation of FRP confining pressure. The present study is dedicated to the development of a new dilation model for both full and partial confinement systems, which takes into account the substantial impact of non-uniform distribution of concrete transversal expansion, a scientific topic not yet addressed comprehensibly in existing formulations. For this purpose, a reduction factor was developed in the determination of the efficiency confinement parameter, by considering available experimental results. Furthermore, based on a database of FRP fully/partially confined concrete, a new analytical relation between secant Poisson’s ratio and axial strain was proposed. To evaluate the reliability and predictive performance of the developed dilation model, it was applied on the simulation of experimental tests available in the literature. The results revealed that the developed model is capable of predicting the experimental counterparts with acceptable accuracy in a design context.